Kontribusi Self Control terhadap Kecenderungan Perilaku Cyberloafing pada Pegawai RS di Kota Bukittinggi - Wahyu Setiawan; Mario Pratama (RC-INSTITUT, 2020)
This study aims to determine the contribution of self-control to the tendency of cyberloafing behavior in hospital employees in the city of Bukittinggi. The research design used in this study is a quantitative research method. The population in this study is the hospital administration staff in the city of Bukittinggi and the sampling technique using a purposive sampling technique with several criteria determined so that the number of subjects was 52 people. In this data collection using self-control scale and the tendency of cyberloafing behavior using simple linear regression analysis techniques. From this study, the percentage contribution was 28.5% with a value of F = 19.957 and p = 0.000 (p <0.05). Thus the hypothesis is accepted so that it can be concluded that there is a very significant negative contribution between self-control towards the tendency of cyberloafing behavior in hospital employees in Bukittinggi City.